Local Emissions and Regional Wildfires Influence Refractory Black Carbon Observations Near Palmer Station, Antarctica - Khan, Alia L.; Klein, Andrew G.; Katich, Joseph M.; Xian, Peng (Frontiers in Earth Science, 2019)
Antarctica is often regarded as the most pristine continent on Earth. However, local human activity can be significant point sources of production of contaminants, as well as light absorbing aerosols, such as black carbon (BC). In May 2015, over the Austral fall season (at the beginning of the accumulation season), surface snow was sampled at eight sites along a 1.7 km transect extending from Palmer Station, Antarctica. Two additional sites were sampled on Biscoe Point 14 km from the station. Snow samples were analyzed for refractory black carbon (rBC) with a Single Particle Soot Photometer (SP2). rBC concentrations increased with proximity to the Palmer Station 1.2 - 16.5 µg-rBC/L-H2O (4.7 ± 4.9 µg-rBC/L-H2O) and were higher than other studies of rBC in snow, such as in the McMurdo Dry Valleys, Antarctica (MDV) and the Clean Air Sector of the South Pole Station (CAS-SP), except on the more remote Biscoe Island, 0.4 - 1.2 µg-rBC/L-H2O, which had similar background concentrations to the MDV and CAS-SP, 0.3 - 1.2 (0.6 ± 0.3 µg-rBC/L-H2O) and (0.14 – 0.80 µg-rBC/L-H2O), respectively. However, concentrations were lower than previous observations at South Pole Station downwind of the generator and long the runway (6.6 – 7000 µg-rBC/L-H2O). Palmer Station is located on the southwestern coast of Anvers Island which lies off the western coast of the Antarctic Peninsula at 64° 46’S, 64° 03’ W. Comparison with the Navy Aerosol Analysis Prediction System (NAAPS) model show that wildfire smoke may have reached this region of the Antarctic continent during the time period of the deposition of this seasonal snow, suggesting the increase in rBC may be a combination of local combustion of fossil fuels and regional wildfires. Although significant increases in rBC concentrations are found within a km of Palmer Station, like the South Pole Station, rBC is limited to a few kms from the station. Additionally, these measurements of rBC, which may be the only BC measurements in snow on the Antarctic Peninsula, show that background levels are similar to other locations on the continent.